Upaya Pendapatan Keluarga Terhadap Usaha Makanan Khas Emping Melinjo Selayar - Raden Sri Aktesa; Irwanti Said (Jurnal Berita Sosial, 2023)
Increasing family income through the typical emping food business is a family income business. The type of research used is descriptive qualitative research, using a sociological and social welfare approach. The data sources of this research are primary data sources and secondary data sources, then the data collection methods used are observation, interviews, and documentation methods. Data processing and analysis techniques are carried out through three stages, namely: data reduction, data presentation, and drawing conclusions. The results showed that: first, the process of managing the typical melinjo emping food in the Selayar Islands, namely by carrying out several stages, namely from providing raw materials for melinjo fruit, providing equipment used when producing melinjo fruit. The processing process begins with heating the melinjo fruit, flattening it, drying it and packing it. Second, efforts to increase family income in the Selayar Islands are marketing melinjo chips to retailers, collectors and also directly to consumers. Selling price and provide good service.